A date for mad Mary [videorecording (DVD)] - Thornton, Darren; Kerslake, Seána; Lee, Tara (Actress); Bailey, Charleigh (Wolfe, 2017)
When Mary McArdle returns to her small Irish home town after a short spell in prison for something she'd rather forget, everything and everyone seems different. Her best friend Charlene is about to get married, and Mary is the maid of honor. When Charlene refuses Mary a 'plus one' on the grounds that she can't find a date, Mary becomes determined to prove her wrong. But her attempts at dating are a disaster, until she meets Jess, a lesbian wedding photographer, and everything changes.